2023
DOI: 10.1002/prot.26500
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of large Aβ16–22 aggregates at atomic details and potential of mean force associated to peptide unbinding and fragmentation events

Abstract: Atomic characterization of large nonfibrillar aggregates of amyloid polypeptides cannot be determined by experimental means. Starting from β-rich aggregates of Y and elongated topologies predicted by coarse-grained simulations and consisting of more than 100 Aβ16-22 peptides, we performed atomistic molecular dynamics (MD), replica exchange with solute scaling (REST2), and umbrella sampling simulations using the CHARMM36m force field in explicit solvent. Here, we explored the dynamics within 3 μs, the free ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Aggregates involving more than 100 of Aβ 16À22 that formed in these CG simulations were then further studied at the all-atom level using REMD simulations, which revealed slow β-strand structuring with a dominance of antiparallel over parallel β-sheets. 184 In 2019, similar results were reported when OPEP was combined with hydrodynamic interactions in an offlattice approach. 185 This approach primarily sampled elongated aggregates formed through a two-step nucleation mechanism, where initially disordered aggregates fused to elongate the amorphous prefibrillar aggregates.…”
Section: All-atom and Cg Opep Simulations By The Derreumaux Labsupporting
confidence: 53%
See 1 more Smart Citation
“…Aggregates involving more than 100 of Aβ 16À22 that formed in these CG simulations were then further studied at the all-atom level using REMD simulations, which revealed slow β-strand structuring with a dominance of antiparallel over parallel β-sheets. 184 In 2019, similar results were reported when OPEP was combined with hydrodynamic interactions in an offlattice approach. 185 This approach primarily sampled elongated aggregates formed through a two-step nucleation mechanism, where initially disordered aggregates fused to elongate the amorphous prefibrillar aggregates.…”
Section: All-atom and Cg Opep Simulations By The Derreumaux Labsupporting
confidence: 53%
“…Their findings demonstrated that hydrodynamic interactions significantly influenced the aggregation process by causing fluctuations in oligomer sizes due to the fusion and fission of aggregates. Aggregates involving more than 100 of 1622$$ {\mathrm{A}\upbeta}_{16-22} $$ that formed in these CG simulations were then further studied at the all‐atom level using REMD simulations, which revealed slow β‐strand structuring with a dominance of antiparallel over parallel β‐sheets 184 . In 2019, similar results were reported when OPEP was combined with hydrodynamic interactions in an off‐lattice approach 185 .…”
Section: Review Of Simulation Studies On Amyloid Aggregationmentioning
confidence: 60%
“…Cluster C7 is consistent with the low β-signal during the lag phase observed by means of experiments 9 and MD and REST2 simulations. 42 We never trapped stable oligomers of small sizes with β-sheet (cluster C2)…”
Section: Resultsmentioning
confidence: 99%
“…35 Molecular simulations on large oligomers showed that Aβ16-22 formed metastable well-structured βbarrels and perpendicular β-sheets. [36][37][38] Overall, the experimental times for primary nucleation and secondary nucleation composed of fragmentation and surface-catalysed effects 39,40 replica exchange with solute tempering, 41,42 metadynamics, 43,44 and path sampling 31 with different protein representations and force fields were used to overcome the free energy barriers involved in each microscopic event. However, metadynamics efficiency depends on the definition of collective variables, path sampling technique depends on the order parameters, and the number of replicas used in REMD increases substantially with the number of degrees of freedom.…”
Section: Iintroductionmentioning
confidence: 99%
“…Therefore, the search for complex order parameters may become an intensive area of research in the theoretical physical chemistry community. Although this perspective focuses on unbiased all-atom simulations, we would be remiss not to mention the important role played by coarse-grained simulations in describing phenomena taking place at longer and larger length scales or the role played by alpha-fold . It is also anticipated that our understanding of amyloid aggregation will be significantly improved by studying longer model peptides, which exhibit β-arcs in the fibril state, see Figure e.…”
Section: Discussionmentioning
confidence: 99%